The Good Samaritan and his genes - Rolston, Holmes, 1932-2025, author; W.B. Eerdmans Publishing, publisher (Colorado State University. Libraries, 2004)
The Good Samaritan helping non-genetically related other does not fit well into a Darwinian framework. Some biologists claim he is constitutionally (=genetically) unable to act for the victim's sake. There must be a self-interested account. The Samaritan, deceived about his motives, is rewarded with reproductively profitable reputation. But such behavior, praised and imitated, jumps genetic lines and there is no differential survival advantage.
Keywords: genes; hypothalamus; limbic system; ethics; biology; evolution; morality; religion; Christianity